DEFINITION OF THE STRATEGIC DIRECTIONS FOR REGIONAL ECONOMIC DEVELOPMENT ON THE EXAMPLE OF THE MOSCOW OBLAST - Dmitriy V. Mikheev; Karina A. Telyants; Elena N. Klochkova; Olga V. Ledneva (Статистика и экономика, 2016)
This article distinguishes methods applied to a deﬁnition of the strategicdirections for regional economic development on the economic basestatistical analysis identiﬁed sources of competitive advantage and disadvantage for the region, main risks for economic growth. The methodswere approved via the research work on the deﬁnition of the prioritiesand target goals for the Moscow Oblast economic development andframework improvement for strategy planning and public regulations.